Asymmetric syntheses of polysubstituted homoprolines and homoprolinols. Issue 48 (2nd December 2015) - Csatayová, Kristína; Davies, Stephen G.; Figuccia, Aude L.A.; Fletcher, Ai M.; Ford, J. Gair; Lee, James A.; Roberts, Paul M.; Saward, Benjamin G.; Song, Haewon; Thomson, James E.
Abstract: Complementary protocols for the diastereoselective syn - and anti -dihydroxylations of enantiopure dihydropyrrole scaffolds were used as the key steps in the asymmetric syntheses of several polysubstituted homoprolines and homoprolinols. The requisite dihydropyrroles were prepared in three steps from commercially available sorbic acid via either hydroamination or aminohydroxylation of the corresponding tert -butyl ester, followed by ring-closing metathesis. Subsequent olefinic oxidation and deprotection gave access to the corresponding enantiopure homoprolines [(2 S, 3 S, 4 R )-dihydroxyhomoproline, (2 S, 3 R, 4 R )-dihydroxyhomoproline and ( S, S, S )-3-amino-4-hydroxy-homoproline], enantiopure α-hydroxy-homoprolines [3, 6-dideoxy-3, 6-imino-d -allonic acid and 3, 6-dideoxy-3, 6-imino-d -gulonic acid] and enantiopure homoprolinols [1, 4-dideoxy-1, 4-imino-l -allitol and ( S, S, S )-3-amino-4-hydroxyhomoprolinol] as single diastereoisomers in good overall yields. Graphical abstract: